2016
DOI: 10.3892/mmr.2016.5706
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of Cirsium setidens extract on oxidative stress in human mesenchymal stem cells

Abstract: Human mesenchymal stem cells (MSCs) may be used in cell-based therapy to promote neovascularization for the treatment of ischemic diseases. However, high levels of reactive oxygen species (ROS) derived from the pathophysiological ischemic environment induce senescence and apoptosis of MSCs, resulting in reduced functionality and defective neovascularization. Therefore, the present study aimed to determine the protective effects of Cirsium setidens, a natural product, on oxidative stress-induced apoptosis in MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
0
23
0
2
Order By: Relevance
“…Recently, a number of studies have been reported that aimed to improve the survival rate of MSCs thereby overcoming the limitations of stem cells as cell‐based therapeutic agents. Treatment with Cirsium setidens extract suppressed H 2 O 2 ‐induced ROS generation in MSCs and increased their survival rate . Berberine also exhibited protective effect against oxidative stress‐induced apoptosis in MSCs .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, a number of studies have been reported that aimed to improve the survival rate of MSCs thereby overcoming the limitations of stem cells as cell‐based therapeutic agents. Treatment with Cirsium setidens extract suppressed H 2 O 2 ‐induced ROS generation in MSCs and increased their survival rate . Berberine also exhibited protective effect against oxidative stress‐induced apoptosis in MSCs .…”
Section: Discussionmentioning
confidence: 92%
“…Treatment with Cirsium setidens extract suppressed H 2 O 2 -induced ROS generation in MSCs and increased their survival rate. 23 Berberine also exhibited protective effect against oxidative stress-induced apoptosis in MSCs. 24 Our results also revealed that NAC, a known antioxidant, exerted protective effect against H 2 O 2 -induced apoptosis in MSCs.…”
Section: Discussionmentioning
confidence: 96%
“…Apocynin, a phenolic compound, partially reverses the ageing process and enhances the potential for osteogenesis in ageing MSCs by suppressing NOX . Both lycopene and Cirsium setidens pretreatments suppressed H 2 O 2 ‐induced ROS generation and increased survival of MSCs by attenuating the phosphorylated p38‐MAPK, JNK, ATM and p53 signalling pathways . Berberine, a natural isoquinoline quaternary alkaloid extracted from the Chinese herb Huanglian, significantly prevents H 2 O 2 ‐induced apoptotic progression by reducing ROS production and levels of apoptosis‐related proteins, while increasing SOD activity and p‐AKT and Bcl‐2 levels .…”
Section: Strategies To Control Ros Levels For Msc Fates In Vitro and mentioning
confidence: 99%
“…MSC therapy is considered a novel and promising strategy for the treatment of ischemic stroke, and may exert neuroprotective effects and promote the repair of neurons by secreting various neural trophic factors and replacing damaged neurons (4). However, the ischemic microenvironment negatively influences the survival rate of transplanted MSCs in injured CNS conditions due to oxidative stress (5,6). Thus, improving the survival of MSCs during oxidative stress may improve the efficacy of MSC-based therapies.…”
Section: Introductionmentioning
confidence: 99%